Propuesta de mejora del proceso de samblasting interno en el tanque 54000-2 de Ecopetrol en Neiva – Huila (2021)
Title: Proposal to improve the internal sandblasting process in the 54000-2 tank of Ecopetrol in Neiva - Huila Author: Damiler Stiven Vargas Cleves. In the activities carried out at the Ecopetrol SA stations, in the maintenance area, we find activities where the greatest exposure to risks occurs. The intervention and maintenance activity of storage tanks or vessels within its different stages, from cleaning the vessel of stored material, metalworking activities, sandblasting or shot blasting activities and application of coatings, installation of measuring equipment or instruments. In the execution of these activities of sandblasting or internal blasting that are framed within the activities in confined spaces, the operator who executes this activity has a method of supplying air from a compressor to a CO indicator to a filter or lung. that carries air to his diving suit. Based on the aforementioned, an evaluation of a design to supply clean air to the operator who performs sandblasting or internal blasting activities in the vessel tanks was carried out. Key words: Supply, filter, CO, redesign